2017
DOI: 10.1177/1010428317731280
|View full text |Cite
|
Sign up to set email alerts
|

Association between Vitamin D receptor (Cdx2, Fok1, Bsm1, Apa1, Bgl1, Taq1, and Poly (A)) gene polymorphism and breast cancer: A systematic review and meta-analysis

Abstract: The purpose of this systemic review and meta-analysis was to examine the relationship between VDR gene polymorphisms and breast cancer. Literature was searched through PubMed database, Google scholar, and the web of knowledge from December 2015 to January 2017 and consists of 34 studies (26,372 cases and 32,883 controls). All statistical measures were done using STATA version 11.2. The heterogeneity among studies was tested using I statistics. Mantel-Haenszel method and DerSimonian-Laird method were used to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 57 publications
(52 reference statements)
1
25
0
1
Order By: Relevance
“…The FokI site is located in a coding exon at the start of the gene and could alter the structure of the VDR gene . It has been demonstrated that VDR gene polymorphisms are associated with several diseases such as hepatitis, multiple sclerosis and breast cancer . The relationship between CRF and VDR gene polymorphisms has been studied.…”
Section: Discussionmentioning
confidence: 99%
“…The FokI site is located in a coding exon at the start of the gene and could alter the structure of the VDR gene . It has been demonstrated that VDR gene polymorphisms are associated with several diseases such as hepatitis, multiple sclerosis and breast cancer . The relationship between CRF and VDR gene polymorphisms has been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies suggest a protective effect of vitamin D on cancer risk and progression [6,7], but clinical and epidemiologic studies have reported controversial results [8][9][10][11][12]. However, the available evidences that vitamin D levels may affect breast cancer survival [13,14] are sufficient to suggest that vitamin D status should be monitored.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a growing literature on the effects of vitamin D/VDR outside of its traditional role in calcium and phosphorus homeostasis. It has been demonstrated that VDR gene polymorphisms are associated with various diseases such as breast cancer , chronic kidney disease , diabetes mellitus , renal cancer , immunodeficiency , Behcet's disease , psychosis , and lupus . Unfortunately the results have often been conflicting; for this reason, a clearer understanding of the nontraditional role of vitamin D/VDRs is becoming ever more important for those of us who work in renal medicine.…”
Section: Discussionmentioning
confidence: 99%